Recent results of cetuximab use in the treatment of squamous cell carcinoma of the head and neck - Perri, Francesco (Dove Medical Press, 2009)
Cetuximab is a chimeric monoclonal antibody that targets the epidermal growth factor receptor. The role of cetuximab is paramount in several subsets of head and neck cancer. In particular, the EXTREME study has indicated cetuximab as the only drug to improve survival when associated with cisplatin and 5-fluorouracil in patients with recurrent/metastatic disease. Furthermore, cetuximab, both alone and in combination with cisplatin, is active in patients with recurrent/metastatic disease who have failed prior platinum-based chemotherapy. Cetuximab, given in association with radiation therapy, is a treatment of choice in first-line therapy of patients with locally advanced inoperable disease. In the same setting, the role of induction chemotherapy has gained considerable interest over the last few years and a number of efforts are being pursued to optimally integrate induction chemotherapy with radiation therapy plus cetuximab. The combination of cetuximab and other targeted therapies is among the most promising new perspectives for patients with head and neck cancer.